IL-1 Receptor-Associated Kinase Signaling and Its Role in Inflammation, Cancer Progression, and Therapy Resistance - Jain, Ajay; Kaczanowska, Sabina; Davila, Eduardo (Frontiers in Immunology, 2014)
Chronic inflammation has long been associated with the development of cancer. Amongst the various signaling pathways within cancer cells that can incite the expression of inflammatory molecules are those that activate IL-1 receptor associated kinases (IRAK). The IRAK family comprises of four family members, IRAK-1, IRAK-2, IRAK-3 (also known as IRAK-M), and IRAK-4, which play important roles in both positively and negatively regulating the expression of inflammatory molecules. The wide array of inflammatory molecules that are expressed in response to IRAK signaling within the tumor microenvironment regulate the production of factors that promote tumor growth, metastasis, immune suppression and chemotherapy resistance. Based on published reports and compelling preliminary data, we propose that the dysregulated activation of the IRAK signaling pathway in cancer cells contributes to disease progression by creating a highly inflammatory tumor environment. In this article, we present both theoretical arguments and experimental data in support of this hypothesis.